2019
DOI: 10.1097/spc.0000000000000442
|View full text |Cite
|
Sign up to set email alerts
|

Recent research on the social network concept and cancer

Abstract: Purpose of reviewThis review covers articles in 2018 and early 2019 that employed the concept of networks and social interactions in research on how patients with cancer cope, receive and respond to medical treatment and allied support. The use of social aspects, and more formally the method of social network analysis for research on social aspects of cancer is quite new. Although we paid special attention to articles that used formal social network analysis, we noted that those articles cover just over a quar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 69 publications
(347 reference statements)
0
8
0
Order By: Relevance
“…A breadth of studies have suggested the important role of social networks in maintaining physical and mental health ( Peer and Hillman, 2014 ; Latkin and Knowlton, 2015 ; Jones and Storksdieck, 2019 ; Lin et al, 2019 ), but scholars have yet to explore such an effect further ( Hunter et al, 2019 ; Chen Y. T. et al, 2021 ). Originally, the relation between social networks and individuals’ physical and mental health was viewed from two perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…A breadth of studies have suggested the important role of social networks in maintaining physical and mental health ( Peer and Hillman, 2014 ; Latkin and Knowlton, 2015 ; Jones and Storksdieck, 2019 ; Lin et al, 2019 ), but scholars have yet to explore such an effect further ( Hunter et al, 2019 ; Chen Y. T. et al, 2021 ). Originally, the relation between social networks and individuals’ physical and mental health was viewed from two perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of adult cancer and cancer survivor care, the number of studies applying a text network analysis to confirm the knowledge structure and overall research trends in the field of interest have increased over the past 10 years [16,[22][23][24][25]. However, few studies that were published in 2017 applied a network analysis method to child and adolescent cancer survivors [15].…”
Section: Introductionmentioning
confidence: 99%
“…Exploiting a text network analysis to study research trends provides useful information with new ideas for future research [ 15 , 16 ]. These results can be used to form a body of knowledge by quantitatively analyzing a large number of papers and qualitatively interpreting the discovered knowledge structure to identify a certain pattern in the scattered data [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some work indicates that larger social networks can protect against mortality in cancer survivors [ 31 ] and ease burden for caregivers [ 18 ]. Size of network alone, however, is unlikely to explain the buffering influence of social support independent of network membership and quality and quantity of interactions [ 25 ].…”
mentioning
confidence: 99%
“…Social network assessment measures used in oncology populations are secondary analyses of retrospective data, or prospective studies that collect information about support at baseline only [ 16 , 25 ] and tend to rely on general measures of social integration or participation (e.g., marital status, volunteering, church attendance) and/or static measures of functional social support (e.g., global ratings of perceived support) [ 19 ]. While informative, these studies are limited by a lack of robust egocentric network data that are necessary for drawing conclusions about the structure and compositions of real-world support networks, including information about relationships and ties between personal support network members [ 16 ].…”
mentioning
confidence: 99%